PO237 A retrospective review of a tertiary neuroinfectious diseases outpatient clinic. (1st December 2017) - Odunsi, Sola; Fernandez, Cristina; Bonington, Alec; Varma, Anoop
Abstract : Background: Neuroinfections are an emerging subspecialty of neurology. The Neuroinfectious diseases clinic at North Manchester General Hospital (NMGH) was established in 2005, with the aim of providing comprehensive, collaborative management of patients with neuroinfectious disorders. The clinic harnesses the expertise of neurology, infectious diseases including HIV medicine clinicians. Aim: To describe the clinic structure, referral patterns, patient case mix, management strategies and clinical outcomes. Method: We conducted a retrospective case review of patients attending the Neuroinfectious diseases clinic at NMGH between 1 st January 2011 and 31 st December 2012. Results: 61 patients were seen in this monthly clinic during our study period (40 HIV positive, 20 non-HIV, 1 refused testing). The average age was 47.4 years. HIV positive patients were most commonly referred with undiagnosed neurological symptoms. HIV negative patients were most commonly referred as outpatient follow-up after a hospital admission. 82.5% of HIV positive patients had atleast 1 new diagnosis after attending, compared to 45% of HIV negative patients. The most common diagnoses amongst HIV positive patients was movement disorders. Conclusion: With the intervention of a speciality Neuroinfectious diseases clinic there is a dramatic increase in identification and appropriate management of neurological disorders in these patients, helping optimise patient care.